Comedy in Russian and Belarusian drama at the beginning of 21st century (the problem of genre modified) - Goncharova-Grabovskaya, Svetlana Ya. (Journal of the Belarusian State University. Philology, 2022)
The specificity of the comedy genre model in Russian and Belarusian dramaturgy at the present stage is revealed. The fact of the search for new means, techniques and mechanisms for creating the comic in the reflection of reality is stated. Comedy strives, on the one hand, to preserve its genetic qualities (the form of the comic, which determines the type of character and conflict, the aesthetic principles of comedy techniques), and on the other hand, to violate them. Today, comedy of a humorous mode still dominates, in which the traditions of the genre that have been established in the last century continue. The field of humour expands its boundaries, touches upon problems related to the field of satire. The blurring of the line between comedy and drama is intensifying, there is a process of not only genre synthesis (comedy tends to drama, drama to comedy), but also genre mutation (comedy goes beyond the genre and acquires the qualities of adjacent genres that are not inherent in it by nature). There is a rupture of the dramatic fabric, a modification of the comedy plot. The microstructure of the comedic action is dramatised, giving the play a new character. Genre indicators of both the semantic (types of character and conflict, the nature of laughter, the author’s assessment) and morphological (plot structure and intonation-speech organisation of the text) levels undergo transformation. The object of criticism is the problems of society concerning the crisis of private life, which is more typical of drama. The artistic structure of the play is unconventional for comedy (genre tonality is erased, there is no pronounced external comedy basis). However, the author dresses the dramatic plot in a comic form, showing the realities of reality. This is evidenced by such dramatic works as «Poor people, damn it» by S. Reshetnikov, «Return of the hero» by A. Seversky, «Rape me» by I. Vaskovskaya, «Sun line» by I. Vyrypaev, «Harvest» by P. Pryazhko, «Live to see the premiere» by N. Rudkovsky, «Trickster club» by V. Olkhovskaya and others.
Keywords: comedy; Russian and Belarusian dramaturgy; modification of genre structure; genre; distortion of literary canon